Public Transportion Crisis in Bandar Lampung - Ida Bagus Ilham Malik (International Conference on Engineering and Technology Development (ICETD), 2013)
The increase number of personal vehicle is not comparable with the growth of public transportation. Though the number of civil has increased rapidly and followed by the increase of people mobility from one place to another. This immeasurably mobility must be facilitated by public transportation in order that the traffic is not crowded by private vehicle.  Because of the increasing personal vehicle user’s, it will have an impact on improvident of using motor cycle  fuel along with it traffic jam that causing time and costs improvident and it is also makes an environmental pollution. Therefore, the growth of public transportation on the city must be held as soon as possible in order to respond increasingof the townspeople, increasingthe number of people mobility from one place to another andincreasing the motor cycle user’s.